(untitled) (Research, Society and Development, 2022)
This article aims to analyze information on entrepreneurship and innovation from federal universities (UF), classified as entrepreneurial universities. This being exploratory research, it was sought from a qualitative and quantitative study, based on content analysis, to detect the results of entrepreneurial actions, presented in the management reports made available by universities. For this, we conducted a multiple case study focusing on information and entrepreneurial actions in the academic environment. From the universe of sixty-six federal universities, those that were in the best positions in the Ranking of Entrepreneurial Universities (RUE) 2021, for each geographic region of Brazil, were selected. This analysis made it possible to understand the characteristics of entrepreneurial universities that are transformed to meet the demands of society. The presentation of data and actions relevant to the achievement of results is a direct demonstration of the transformation that is sought in an environment of construction of Entrepreneurial Universities in all regions, being reflected in the perception of students and other stakeholders. As an academic contribution, this study relates the characteristics of entrepreneurial universities and integrates these characteristics into dimensions to understand the strategic objectives for traditional universities to become more entrepreneurial and can serve as a starting point for other empirical studies.